Effects of Dance Music on Motor Skills and Balance in Children: An Observational Cohort Study - Tadashi Ito; Hideshi Sugiura; Kentaro Natsume; Sho Narahara; Yoshifumi Sugimoto; Emi Matsuzawa; Hitomi Fujita; Yuji Ito; Kazunori Yamazaki; Natsuki Shimizu; Koji Noritake; Nobuhiko Ochi (MDPI AG, 2024)
Background/Objectives: During the COVID-19 pandemic, children in Japan were restricted from sports and outdoor activities. Regular physical activity is essential for healthy growth and development in children, with recommendations advocating for activities such as strength training. However, the long-term effects of the restrictions have not been fully investigated. This study aimed to evaluate the effectiveness of an "exercise class", specifically a dance program, designed to improve motor function in elementary school children affected by the coronavirus disease 2019 (COVID-19) pandemic, which may have compromised their motor function. Methods: The dance program was developed by a sports science teacher, a professional dancer, and a physical therapist, and it was evaluated in a community-based participatory study. Trained dance instructors conducted one-hour dance sessions in a medical center, held once a week for two months from June to August 2023. A physical therapist and dance instructors led the elementary school children. Outcome measures included grip strength, lower extremity muscle strength, back muscle strength, dynamic balance function during movement, physical activity time, and body fat percentages. Descriptive statistics were used for analysis. Results: Twenty-four children aged 6-9 years participated in the exercise class over a two-month period. Improvement was observed in grip strength, lower extremity muscle strength, and dynamic balance function during movement. However, physical activity time, body fat percentages, and back muscle strength did not change. Conclusions: The results indicated a significant improvement in motor skills. Dance is an inexpensive program that elementary school children can enjoy while improving their motor skills.